From Mining to Marketing: How Pi Currency Supports Sustainable Digital Advertising in Iringa Municipality - Lusekelo Kibona (IJIES (International Journal of Innovation in Enterprise System), 2025)
The rapid growth of digital technology has revolutionized the way businesses market their products and services. However, traditional digital advertising models often face challenges such as ad blockers, intrusive ads, and lack of transparency. To address these issues, innovative solutions are emerging, including the use of cryptocurrencies like Pi Network. The aim of this study was to explore the role of Pi currency in advancing sustainable digital advertising in Iringa Municipal, focusing on its adoption, cost efficiency, and associated challenges. With a sample size of 60 participants, the research examined key indicators, including awareness and adoption, the impact on cost efficiency, and barriers to implementation. Findings revealed varying levels of awareness and adoption, with perceived benefits driving its gradual acceptance. The use of Pi currency demonstrated potential in reducing advertising transaction fees and enabling smaller businesses to access digital advertising platforms. However, challenges such as technical integration, regulatory concerns, and accessibility hindered its mainstream adoption. Insights from respondents underscored the need for strategic efforts to enhance the integration of Pi currency into existing digital marketing systems while addressing barriers to adoption. This study contributes to the discourse on integrating blockchain-based digital currencies into marketing practices, offering a foundation for future research on sustainable and innovative advertising solutions.